Digital Flaming Phenomenon: Flamer Reasons Behind “Freedom of Expression” on Social Media - Arisanty, Melisa; Riady, Yasir; Robiansyah, Anton; Permatasari, Sri Maulidia; Pangesti, Nadya Rahma (Universitas Islam Negeri Raden Intan Lampung, 2023)
Generally, people use social media as a real-life reference. Social media provides freedom to share information, usually called 'content'. Every day, millions of pieces of information are absorbed and enjoyed by many people. This includes 'rubbish' information such as verbal abuse, swearing, and blasphemy. Freedom of expression has gone beyond borders. This phenomenon is called Digital Flaming. Digital Flaming is a detrimental behavior, both for the flamers and their victims. The impact that occurs most often attacks a person's mental state. Digital flaming occurs due to specific motivations or factors. This research aims to critically discuss a person's motivations for digital flaming on social media. The method used is qualitative, conducted in-depth interviews and focus group discussions with informants. This research shows that digital flaming occurs based on six motivations: fanaticism, incitement, spontaneous emotions, low literacy, anonymity through second accounts, and lack of empathy. The causal factors and various motivations identified in this research are the basis for determining strategies for preventing flaming behavior on social media. This way, we can minimize flaming on social media in the future.